Kompetensi Guru Pendidikan Agama Kristen Menyikapi Post-Truth Pada Era Disrupsi Teknologi Informasi - Karlau, Sensius Amon; Rukua, Ivo Sastri (Sekolah Tinggi Teologi Simpson Ungaran, 2023)
This study aims to discuss technological disruptions that need to be addressed by Christian education teachers with adequate competence. Apparently, the rapid development of technology has created a dilemma for some Christian education teachers in Indonesia because they do not yet have adequate digital competence. Therefore, the qualitative method and the literature approach along with the thought analysis step are used to explore theoretical aspects and empirical facts. This is the effort made in several literatures such as books and journals. The results show that Christian religious education teachers should continue to improve their competence, including digital, spiritual and multiliteracy competencies that are responsive to the influence of Post-Truth in the era of technological disruption. Furthermore, Christian education teachers are responsible for utilizing the development of information technology, optimistic in increasing digital competence, in order to concretize the principles of multiliteracy education in a critical-reflective and effective manner on a variety of information for students in relation to the existence and social relations of a pluralistic society.